Inhaled bacteriophage-loaded polymeric microparticles ameliorate acute lung infections. (November 2018) - Agarwal, Rachit; Johnson, Christopher; Imhoff, Barry; Donlan, Rodney; McCarty, Nael; García, Andrés
Abstract Lung infections associated with pneumonia, or cystic fibrosis caused byPseudomonas aeruginosa or other bacteria, result in significant morbidity and mortality, in part owing to the development of multidrug resistance, also against last-resort antibiotics. Lytic bacteriophages (that is, viruses that specifically kill bacteria) can reduce lung-associated infections, yet their clinical use is hindered by difficulties in delivering active phages to the deep lung. Here, we show that phage-loaded polymeric microparticles deposit throughout the lung via dry powder inhalation and that they deliver active phages. Phage-loaded microparticles effectively reducedP. aeruginosa infections and the associated inflammation in wild-type and cystic fibrosis transmembrane-conductance-regulator knockout mice, and rescued the mice from pneumonia-associated death. These polymeric microparticles might constitute a clinically translatable therapy for eradicating hospital-acquired lung infections and infections associated with cystic fibrosis. Polymer microparticles loaded with lytic bacteriophages that deposit throughout the lung via dry powder inhalation rescue mice from pneumonia-associated death.